Pengaruh Perlakuan Termal Terhadap Karakteristik Aspal Komposit Berbasis Silika Sekam Padi - Nita Susanti; Juniati Br Simbolon; Simon Sembiring; Posman Manurung (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2020)
Synthesis and characterization of asphalt has been modified with silica rice husk with temperature variations of 200, 250, and 300oC. Silica is obtained from rice husk using the sol gel method. Furthermore asphalt and silica are solidified at 110oC. The experiment was conducted to determine the effect of temperature on the microstructure, structure, and functional groups of modified asphalt. SEM analysis shows asphalt modification with a temperature of 300oC in the form of different clumps. XRD analysis showed the phase formed from each temperature was an amorphous phase. The result of the FTIR analysis showed that the functional groups seen in the modified asphalt samples were Si-OH, Si-O-Si, Si-O, and C-H. The compressive strength carried out showed the strength of asphalt again cracks became stronger as the temperature increased.